2005
DOI: 10.1095/biolreprod.104.037069
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel and Known Oocyte-Specific Genes Using Complementary DNA Subtraction and Microarray Analysis in Three Different Species1

Abstract: The main objective of the present study was to identify novel oocyte-specific genes in three different species: bovine, mouse, and Xenopus laevis. To achieve this goal, two powerful technologies were combined: a polymerase chain reaction (PCR)-based cDNA subtraction, and cDNA microarrays. Three subtractive libraries consisting of 3456 clones were established and enriched for oocyte-specific transcripts. Sequencing analysis of the positive insert-containing clones resulted in the following classification: 53% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 51 publications
2
62
0
Order By: Relevance
“…Microarray-based gene expression profiling in dairy cattle has been discussed recently (Beerda and Veerkamp, 2006) for studies on oocyte maturation (Dalbiè s-Tran and Mermillod, 2003;Vallee et al, 2005), non-regressed and regressed corpus luteum tissue (Casey et al, 2005), oviduct epithelial cell function (Bauersachs et al, 2003 and, the endometrium during the oestrous cycle , pre-implantation embryonic development (El-Halawany et al, 2004;Ushizawa et al, 2004;Sirard et al, 2005) and embryo-induced transcriptome changes of the endometrium in the pre-and peri-attachment period (Ishiwata et al, 2003;Klein et al, 2006). Briefly, the findings indicate that at the ovarian level, processes are typically controlled Functional genomics applied to dairy cow fertility by genes involved in steroid biosynthesis, oxygen radical metabolism, apoptosis, regulation of cell cycles (including DNA replication and repair), cell structure and tissue remodelling.…”
Section: Recent Transcriptomic Studies On Dairy Cow Fertilitymentioning
confidence: 99%
“…Microarray-based gene expression profiling in dairy cattle has been discussed recently (Beerda and Veerkamp, 2006) for studies on oocyte maturation (Dalbiè s-Tran and Mermillod, 2003;Vallee et al, 2005), non-regressed and regressed corpus luteum tissue (Casey et al, 2005), oviduct epithelial cell function (Bauersachs et al, 2003 and, the endometrium during the oestrous cycle , pre-implantation embryonic development (El-Halawany et al, 2004;Ushizawa et al, 2004;Sirard et al, 2005) and embryo-induced transcriptome changes of the endometrium in the pre-and peri-attachment period (Ishiwata et al, 2003;Klein et al, 2006). Briefly, the findings indicate that at the ovarian level, processes are typically controlled Functional genomics applied to dairy cow fertility by genes involved in steroid biosynthesis, oxygen radical metabolism, apoptosis, regulation of cell cycles (including DNA replication and repair), cell structure and tissue remodelling.…”
Section: Recent Transcriptomic Studies On Dairy Cow Fertilitymentioning
confidence: 99%
“…Several orthologues of known mouse oocyte-specific genes were cloned in the cow (Pennetier et al 2004. Libraries of ESTs preferentially represented in oocytes when compared with somatic tissues were generated by suppressive subtractive hybridisation , Vallee et al 2005. Alternatively, oocyte preferential EST were revealed through differential hybridisation of a bovine oocyte cDNA library with probes from foetal ovaries versus liver or spleen (Yao et al 2004).…”
Section: Oocyte-specific Genesmentioning
confidence: 99%
“…Phylogenetic analysis has indicated that germ cellspecific genes evolve faster than ubiquitous genes (Paillisson et al 2007). Nevertheless, cross-species hybridisation has identified genes conserved between Xenopus, mouse and cow; they are thought to be involved in evolutionarily conserved molecular mechanisms (Vallee et al 2005).…”
Section: Oocyte-specific Genesmentioning
confidence: 99%
“…Recently, a multi-species cDNA microarray containing 3456 transcripts from three distinct oocyte libraries from bovine, mouse, and Xenopus laevis oocytes was used to analyze genes preferentially or commonly expressed between the oocytes of the three species (Vallée et al 2005(Vallée et al , 2006. From 1541 clones conserved in all three species, 268 clones were exclusively expressed in the oocytes of all species.…”
Section: Cross-species Transcriptome Profilingmentioning
confidence: 99%